TEACHING HISTORICAL EMPATHY TROUGH REFLECTIVE LEARNING - Utami, Indah Wahyu Puji (History Department, Semarang State University and Historian Society of Indonesia, 2019)
History does not only teach about certain facts or events that occurred in the past but also teaches about empathy since it emphasizes every aspect of human life. Students could learn about historical empathy trough reflective learning. This research explains teaching historical empathy trough reflective learning, especially teaching social history course. This research was conducted by a qualitative method using a case study design. The researcher collected the data through observation and documentation taken during the Social History Course in the 2016/2017 academic year. Those collected data were then analyzed using a Miles and Huberman interactive model. Based on this research, reflective learning is a model that can be used to teach historical empathy. The role of a lecturer is necessary to promote historical empathy, especially in helping students to make an affective connection to the past.Keywords: empathy, social history, reflective learningÃ‚Â Sejarah tidak hanya mengajarkan tentang fakta atau peristiwa tertentu yang terjadi di masa lalu tetapi juga mengajarkan tentang empati karena itu menekankan setiap aspek kehidupan manusia. Siswa dapat belajar tentang empati sejarah melalui pembelajaran reflektif. Penelitian ini menjelaskan pengajaran empati sejarah melalui pembelajaran reflektif, terutama mengajar kursus sejarah sosial. Penelitian ini dilakukan dengan metode kualitatif menggunakan desain studi kasus. Peneliti mengumpulkan data melalui observasi dan dokumentasi yang diambil selama Kursus Sejarah Sosial di tahun akademik 2016/2017. Data yang dikumpulkan kemudian dianalisis menggunakan model interaktif Miles dan Huberman. Berdasarkan penelitian ini, pembelajaran reflektif adalah model yang dapat digunakan untuk mengajarkan empati sejarah. Peran seorang dosen diperlukan untuk meningkatkan empati sejarah, terutama dalam membantu siswa untuk membuat hubungan afektif dengan masa lalu.Ã‚Â Kata kunci: empati, sejarah sosial, pembelajaran reflektifÃ‚Â Ã‚Â